2023
DOI: 10.1101/2023.03.11.532186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacologic Activation of a Compensatory Integrated Stress Response Kinase Promotes Mitochondrial Remodeling in PERK-deficient Cells

Abstract: The integrated stress response (ISR) is a network of eIF2alpha kinases, comprising PERK, GCN2, HRI, and PKR, that induce translational and transcriptional signaling in response to diverse insults. The PERK ISR kinase regulates mitochondria in response to endoplasmic reticulum (ER) stress. Deficiencies in PERK signaling lead to mitochondrial dysfunction and contribute to the pathogenesis of numerous diseases. We define the potential for pharmacologic activators of other ISR kinases to rescue ISR signaling and p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Our identification of the ISR as the predominant stress-responsive signaling pathway activated by CRISPRi-mediated mitochondrial proteotoxic stress underscores a unique opportunity to target the ISR to correct pathologic mitochondrial dysfunction in etiologically diverse diseases. For example, recent work showed that pharmacologic activation of the ISR kinase GCN2 reduced mitochondrial fragmentation and respiratory chain dysfunction in cells deficient in the ISR kinase PERK ( Perea et al. , 2023a ) – a condition linked to many neurodegenerative diseases including Alzheimer’s disease and Progressive Supranuclear Palsy ( Yuan et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our identification of the ISR as the predominant stress-responsive signaling pathway activated by CRISPRi-mediated mitochondrial proteotoxic stress underscores a unique opportunity to target the ISR to correct pathologic mitochondrial dysfunction in etiologically diverse diseases. For example, recent work showed that pharmacologic activation of the ISR kinase GCN2 reduced mitochondrial fragmentation and respiratory chain dysfunction in cells deficient in the ISR kinase PERK ( Perea et al. , 2023a ) – a condition linked to many neurodegenerative diseases including Alzheimer’s disease and Progressive Supranuclear Palsy ( Yuan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Further, ISR-dependent translational attenuation regulates mitochondrial protein import through the degradation of the core import subunit TIM17A ( Rainbolt et al. , 2013 ; Perea et al. , 2023a ).…”
Section: Introductionmentioning
confidence: 99%